2011
DOI: 10.5194/hess-15-1757-2011
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of soil carbon pools and fluxes in a channelized and a restored floodplain section (Thur River, Switzerland)

Abstract: Abstract. Due to their spatial complexity and dynamic nature, floodplains provide a wide range of ecosystem functions. However, because of flow regulation, many riverine floodplains have lost their characteristic heterogeneity. Restoration of floodplain habitats and the rehabilitation of key ecosystem functions, many of them linked to organic carbon (C) dynamics in riparian soils, has therefore become a major goal of environmental policy. The fundamental understanding of the factors that drive the processes in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 53 publications
(56 reference statements)
2
57
0
Order By: Relevance
“…Further information on this site is given in Woolsey et al [23]. We selected six habitats based on the functional process zones (FPZ) [24] proposed by Samaritani et al [25] to represent the different post-restoration successional stages present at the site. These zones represent a gradient of decreasing flood mechanical impact.…”
Section: Study Areamentioning
confidence: 99%
“…Further information on this site is given in Woolsey et al [23]. We selected six habitats based on the functional process zones (FPZ) [24] proposed by Samaritani et al [25] to represent the different post-restoration successional stages present at the site. These zones represent a gradient of decreasing flood mechanical impact.…”
Section: Study Areamentioning
confidence: 99%
“…Bare gravels with patches of poorly developed soil -FLUVIOSOLS BRUTS -and pioneer vegetation constituted the first habitat (GRAVELS). The second habitat (HERBS) was an area with more developed soils -FLUVIOSOLS JUVENILES -but showing high spatial and temporal heterogeneity (Samaritani et al, 2011) and dominated by tall herbs (Phalaris arundinacea). The third habitat (WILLOW BUSH) was characterised by soils of average depth (FLUVIOSOLS TYPIQUES) and patches of planted willow bushes.…”
Section: Study Sitementioning
confidence: 99%
“…1). Six different habitats were selected based on elevation and distance to the river, soil type, vegetation structure, and impact of restoration (Samaritani et al, 2011). The French soil classification (Baize and Girard, 2009) was preferred over the FAO World Reference Base for Soil Resources (IUSS Working Group WRB, 2006) because the latter does not dis-criminate different types of Fluvisols (the dominant soil taxon within the study site).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…These samples were analysed for NH 4 (flow injection 141 analysis based on alkalinisation and diffusion of NH 3 into an acid carrier followed by 142 colorimetric detection of an indicator dye), NO 3 (direct colorimetry, Navone 1964) and non-143 purgeable organic C (elemental analyser, Skalar Formacs HT and TN). 144 Samaritani et al (2011) presented a study relating variability of C pools and fluxes (CO 2 ) to 145 soil properties, environmental conditions and flood disturbance in a revitalized section of the 146 Thur River. They found that, overall, environmental conditions driven by seasonality and 147 flooding affected soil C dynamics more than soil properties did.…”
mentioning
confidence: 99%